STRATEGI PEMASARAN DAN PENGEMBANGAN COMPETITIVE ADVANTAGE PADA NICHE FIRM : STUDI KASUS US.FROZEN FOOD - Gonga, Tomi (PERFORMA, 2017)
The purpose of this study is to develop competitive advantage in US.frozen food and measuring the position of US.frozen food in the market through internal factor analysis and external factor analysis for implicating strategy that the benchmarked company applied according to the positon of US.frozen food. This study collect data from benchmarked company, US.frozen food’s customer, and US.frozen food’s company member and analyze US.frozen food’s SWOT factor to achieve the position in SWOT quadrant and analyze marketing mix to improve marketing strategy using interview and documentation to collect every data needed with qualitative descriptive approach.The result of this study indicate that the position of US.frozen food is in the WT quadrant and suppose to use defensive strategy which optimized with marketing mix from benchmarked company.